1998
DOI: 10.1161/01.cir.98.5.429
|View full text |Cite
|
Sign up to set email alerts
|

RR Interval Dynamics Before Atrial Fibrillation in Patients After Coronary Artery Bypass Graft Surgery

Abstract: Background-Atrial fibrillation/flutter (AF) is a frequent complication of coronary artery bypass graft surgery (CABG) that leads to increased costs and morbidity. We hypothesized that heart rate variability (HRV), an indicator of cardiac sympathovagal balance, is altered before the onset of postoperative AF. Because nonlinear methods of HRV analysis provide information about heart rate dynamics not evident from usual HRV measures, we also hypothesized that approximate entropy (ApEn), a nonlinear measure of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
5
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 50 publications
7
100
5
3
Order By: Relevance
“…26 Concurrent with the present observations, a recent study also reported on reduced ApEn preceding spontaneous AF episodes in patients after coronary artery bypass surgery. 10 These results suggest that a reduced complexity of R-R interval dynamics is a common finding preceding the onset of AF episodes, independent of the clinical condition and cause of an underlying structural heart disease.…”
Section: Complexity and Correlation Properties Of Hr Dynamics Before Afmentioning
confidence: 69%
See 1 more Smart Citation
“…26 Concurrent with the present observations, a recent study also reported on reduced ApEn preceding spontaneous AF episodes in patients after coronary artery bypass surgery. 10 These results suggest that a reduced complexity of R-R interval dynamics is a common finding preceding the onset of AF episodes, independent of the clinical condition and cause of an underlying structural heart disease.…”
Section: Complexity and Correlation Properties Of Hr Dynamics Before Afmentioning
confidence: 69%
“…[13][14][15][16] A recent study suggested that altered complexity of R-R interval dynamics precedes the AF episodes of patients after coronary artery bypass graft surgery. 10 The trigger mechanisms and pathophysiology of AF may be different between patients with and without organic heart disease and in various clinical situations. The present study was designed to test the hypothesis that altered R-R interval dynamics, as analyzed by new complexity and fractal measures, may also precede the onset of paroxysmal, idiopathic AF.…”
mentioning
confidence: 99%
“…After coronary artery bypass grafting (CABG) the incidence of AF varies from 19 to 27% and is the most common morbidity after this surgery [2]. Thus, with the growing interest in understanding the physiopathologic basis responsible for the occurrence of this arrhythmia, operative techniques have been developed aiming at reducing its incidence [3].…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was seen in the turbulence slope between the AF and control, and none of the traditional frequency and time domain measures differentiated between both; ApEn was significantly lower before AF than during the non-AF hours (p < 0.01). Increased predictability in heart rate behavior, measured by ApEn, also has been reported to precede spontaneous episodes of ApEn after coronary artery bypass surgery [Hogue, Jr. et al, 1998] Analysis of HRV in this study was performed in three sequential 20-minute intervals preceding the onset of postoperative AF (24 episodes in 18 patients). These data were compared with corresponding intervals in 18 sex-and age-matched postoperative control subjects who did not develop AF.…”
Section: Further Applicationsmentioning
confidence: 99%